2016
DOI: 10.1007/s00276-016-1707-9
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and relations of the infraspinatus and the teres minor muscles: a fresh cadaver dissection study

Abstract: ISP muscle body morphology derives from three groups of fibers in two planes. The TM has a parallel organization. Several nerve branches innervate the ISP muscle, whereas only one supplies the TM. The limits between the two muscles bodies consist of an aponeurotic fascia in two-thirds of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 22 publications
5
42
0
Order By: Relevance
“…In the infraspinatus, the tendon fibres of the superior, middle, and inferior partitions formed the conjoint tendon. The muscle fibres of the superior, middle, and inferior partitions according to Fabrizio and Clemente as well as to Bacle et al [1, 7] were identified in agreement with muscle fibre directions. A portion of the deep muscle fibres of the inferior partition overlaid those of the middle partition.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…In the infraspinatus, the tendon fibres of the superior, middle, and inferior partitions formed the conjoint tendon. The muscle fibres of the superior, middle, and inferior partitions according to Fabrizio and Clemente as well as to Bacle et al [1, 7] were identified in agreement with muscle fibre directions. A portion of the deep muscle fibres of the inferior partition overlaid those of the middle partition.…”
Section: Resultssupporting
confidence: 67%
“…For histological assessment, we obtained coronal sections parallel to the tendons of the anterior region and posterior region of the supraspinatus according to Roh et al and Kim et al [10, 17] and sections of the superior, middle, and inferior partitions of the infraspinatus according to Fabrizio and Clemente as well as Bacle et al [1, 7]. These samples were stained with Masson’s trichrome.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The teres minor muscle has fibers running parallel to and inserting on the inferior angle of the scapula (Figure 2). 2 Once the muscle architecture was clearly visible, an image was taken. This procedure was also repeated 3 times on both shoulders.…”
Section: Ultrasoundmentioning
confidence: 99%
“…If the ISP muscle effectively contributed to shoulder abduction, the ISP muscle should exert enough activation at initial range, prior to that of the deltoid muscle. Recent detailed anatomical studies demonstrated that the ISP muscle was anatomically divided into two or three distinct neuromuscular partitions based on differences in their attachment sites, muscle fiber directions, and intramuscular innervations [3,6,15,22,31]. Several authors demonstrated that the anterior-most region of the humeral insertion of the ISP muscle almost reached the anterior margin of the highest impression of the greater tuberosity [22][23][24][25]31].…”
Section: Introductionmentioning
confidence: 99%